“Emotional regulation” or “affective regulation”? - de Jesús Gómez, Ruth Mª; Cornu-Labat, María A. (Frontiers in Psychology, 2024)
In recent decades, there has been an increased interest in psychology to understand the emotional experience. This growing interest has led to a proliferation of terms, among which regulation, intelligence, and emotional competence stand out. Research in these areas has facilitated a better understanding of what emotion entails and how to intervene in it. However, this study highlights that these contributions are insufficient if one aims to understand and intervene in how reality affects each person. In this sense, there is an advocacy for the recovery of the term affectivity, as it addresses all affective experiences and, therefore, is broader and more integrative.